2018
DOI: 10.3389/fnagi.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Royal Jelly Reduces Cholesterol Levels, Ameliorates Aβ Pathology and Enhances Neuronal Metabolic Activities in a Rabbit Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common form of dementia characterized by aggregation of amyloid β (Aβ) and neuronal loss. One of the risk factors for AD is high cholesterol levels, which are known to promote Aβ deposition. Previous studies have shown that royal jelly (RJ), a product of worker bees, has potential neuroprotective effects and can attenuate Aβ toxicity. However, little is known about how RJ regulates Aβ formation and its effects on cholesterol levels and neuronal metabolic activities. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 65 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…The methods of IHC staining have been reported previously (Pan et al, 2018). Briefly, sections were blocked with 3% BSA for 30 min, then incubated with primary antibodies overnight at 4°C, including BACE1 (1:100, Santa Cruz Biotechnology, USA), IDE (1:100, Santa Cruz Biotechnology, USA), β-amyloid (B-4, 1:100, Santa Cruz Biotechnology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The methods of IHC staining have been reported previously (Pan et al, 2018). Briefly, sections were blocked with 3% BSA for 30 min, then incubated with primary antibodies overnight at 4°C, including BACE1 (1:100, Santa Cruz Biotechnology, USA), IDE (1:100, Santa Cruz Biotechnology, USA), β-amyloid (B-4, 1:100, Santa Cruz Biotechnology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, polyphenolic compounds antagonize AGE receptors, mainly RAGE, and facilitate the removal of already formed a,b-dicarbonyl intermediates such as methylglyoxal, promoting the degradation of AGEs [ 37 , 38 , 146 ]. Royal jelly is reported to downregulate the activity of RAGE, the main receptor for AGEs, in an aged model of cognitive impairment [ 147 ]. However, its anti-glycation effect has not been investigated in skeletal muscle yet.…”
Section: Mechanisms Of Action Of Royal Jelly Bee Pollen and Propmentioning
confidence: 99%
“…El-Nekeety et al (2007) concluded that RJ improved the superoxide dismutase activity in male Sprague-Dawley rats and has a protective effect against oxidative stress in a dose-dependent manner. Pan et al (2018) suggested that RJ significantly reduced the levels of plasma total cholesterol and low-density lipoprotein-cholesterol in rabbits.…”
Section: Introductionmentioning
confidence: 99%